2010
DOI: 10.1007/s00540-010-0891-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preoperative oral melatonin medication on postoperative analgesia, sleep quality, and sedation in patients undergoing elective prostatectomy: a randomized clinical trial

Abstract: Preoperative oral melatonin administration decreased pain scores and tramadol consumption and enhanced sleep quality, sedation scores, and subjective analgesic efficacy during the postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
101
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(107 citation statements)
references
References 24 publications
5
101
1
Order By: Relevance
“…(27) Previous studies have shown slight improvements in sleep quality in the early postoperative period when patients were given melatonin compared to a placebo. (18,20,28) However, our study did not demonstrate a significant difference in sleep quality between both groups (p = 0.830).…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…(27) Previous studies have shown slight improvements in sleep quality in the early postoperative period when patients were given melatonin compared to a placebo. (18,20,28) However, our study did not demonstrate a significant difference in sleep quality between both groups (p = 0.830).…”
Section: Discussioncontrasting
confidence: 78%
“…(17)(18)(19) A study by Borazan et al in patients undergoing elective prostatectomy also showed a significant decrease in postoperative pain when a dual-dosing regimen was used. (20) In contrast, studies which used a once-only dosing for melatonin did not show a significant difference in pain scores when compared with a placebo. (21)(22)(23) However, Andersen et al also noted in a recent review article that other factors, including dosage used, administration route and timing of melatonin administration prior to surgery, may affect the effects of melatonin and that further studies were required to demonstrate the dose-response relationship for melatonin.…”
Section: Discussionmentioning
confidence: 94%
“…Most studies gave melatonin 30-100 min before surgery [4, 12, 14, 17-24, 27, 29-31]. One study gave melatonin daily for one month pre-operatively [28], whereas four studies gave melatonin the night before surgery, in addition to the immediate pre-operative dose [5,6,13,15]. Three studies gave melatonin at surgical incision [25,26] or after intubation [32].…”
Section: Resultsmentioning
confidence: 99%
“…Participants had various operations: abdominal [15][16][17]25, Full-text studies excluded (n = 17) -10 studies did not investigate surgical patients -3 studies were protocol studies -2 studies were not randomised -2 studies used melatonin only in combination with other drug interventions 32]; dental [27]; gynaecological [5,6,18,19,30]; ophthalmological [4,14]; orthopaedic [12]; thoracic [28,29]; urological [13]; vascular [26]; and mixed [20][21][22][23][24]31]. The anaesthetic techniques included: general anaesthesia [13,[15][16][17][18][19][20][21][22][23][24][25][26][28][29][30][31][32]; intravenous regional anaesthesia [12]; neuraxial block [5,6,20,26,31]; sedation …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation